From Transformative Travels to Translingual Poetics: the "Ultime voyage" of Victor Segalen and François Cheng - Tan, Xinyi (Dalhousie French Studies)

(untitled) (Department of French, Dalhousie University, 2021)
François Cheng and Victor Segalen are widely acknowledged for their common role of “cultural ambassador” between China and France. However, according to Jean Mouttapa who wrote the preface for Cheng’s book L’Un vers l’autre. En voyage avec Victor Segalen (2008), there exists a “spiritual affinity” between the two authors that connects them in a fundamental way. Focusing on this unusual bond, this article examines how the dual destinations of travel – lieu (Other/Elsewhere) and milieu (Self/Home) – are represented in two poetic creations, namely “Perdre le Midi Quotidien” by Segalen and “Ultime voyage” by Cheng. At the intersection of French and Chinese, the travelers-poets trace and translate the courses of their internal progress through their physical displacements. Drawing on essential concepts from Segalen’s theory such as the Divers and the Exote, my analysis reveals the extent to which Segalen and Cheng’s translingual poetics serve as a powerful vehicle to display and disseminate their positive view of the Self-Other bond.